Investigating the effects of community-based interventions on mathematics achievement of girls from low-income households in Kenya - Hungi, N.; Ngware, M. (2017)
This paper uses difference-in-difference and multivariate analyses procedures to examine the effects of two community-based intervention packages on mathematics achievement of primary school girls from low-income urban households in Kenya. The data involved in this study were collected between 2013 and 2015 from 748 1219 years old primary school girls residing in two major Nairobi slums of Viwandani and Korogocho. These data were part of a larger intervention study that sought to improve schooling outcomes among girls from disadvantaged home backgrounds by providing them with after-school homework support, life skill mentoring and parental counselling. Results reveal intervention effects of between 23 and 26 mathematics score points on a Rasch scale with a mean of 400 a standard deviation of 100. These effects translate to at least one school term of learning for girls in the comparison group. Effect size for one of the intervention packages was small (0.24), while that of the second package was moderate (0.40)
Keywords: Community participation; Equity; Female empowerment; Gender disparities; Numeracy; Poverty; Primary education; Remedial education; _C:Kenya; _authorsString:Second,A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article